THE USE OF REFUSAL STRATEGIES IN WORK PLACE SETTING IN STIA LAN BANDUNG - Khaerunisa Khaerunisa (STKIP Siliwangi, 2013)
This study was conducted to find out the refusal strategies in work place setting by10 employees of STIA LAN Bandung. The questionnaire used was DiscourseComprehension Test (DCT) developed by Beebe et al (1990) in 12 differentsituations. The participants were asked to refusing 12 different situations tosomeone who comes from higher, equal, and lower status. The findings of this studyshow that the participants mostly used indirect strategies in refusing someone’srequest depend on the status in the work place. The findings also shown that theparticipants use 6 different strategies relate with ‘saving face’ and the highestpercentage is regret strategy and the lowest percentage is ‘other’ strategy. Inconclusion, the participants use different strategies; direct strategies to the lowerstatus and indirect strategies to the equal and higher status.Keywords: refusal strategies, Discourse Comprehension Test